Religious humor in evangelical Christian and Mormon culture - McIntyre, Elisha (New York Bloomsbury Academic, 2018)
Evangelicals, Mormons and popular culture -- Introducing the challenges of humor -- Appropriate humor I: blasphemy and belief -- Appropriate humor II: clean and dirty humor -- Appropriate humor III: safe and subversive humor
Includes bibliographical references and index
Reproduktion
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Mormon wit and humor; Evangelicalism -- Humor; Wit and humor -- Religious aspects -- Christianity; Electronic books